An Analysis of the Ethiopian and Rwanda Dairy Projects - Tsorai, Simon (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Ethiopia and Rwanda are developing countries in Africa, and various projects are underway to improve the economic situations. One of the main areas of recent development is agriculture. Agriculture employs a huge part of the working age population in both countries, and the dairy industry is becoming more visible in the recent years. Ethiopia owns one of the largest livestock herd in Africa, and there is a potential in maximizing the milk production. However, poverty is still a huge problem in Ethiopia, and this can only be reduced by investing in the dairy industry to reduce unemployment and increase the food security. The current economic climate in Ethiopia is conducive for expanding investments in the dairy industry, and this can increase and motivate the smallholder farmers. If proper investments are done, then the dairy industry in Ethiopia will yield positive results. Rwanda is a beacon of hope in Africa. The level of good governance in the country is spectacular and sets the pace for other afican countries to follow. Rwanda is advancing its economy on a larger scale, and the willingness of the government to modernize its policies is something worth noticing. The dairy industry was in a bad state, but the USAID intervention has made tremendous efforts to modernize the industry. The farmers, feed processors and consumers have benefited from the training conducted by the USAID. If Rwanda continues with the same pace, then the dairy industry will flourish, and they will be able to compete with their neighbors. To flourish, both countries need to invest more in new technologies and education since these two are important in the long run. Keywords: Interventions, Investment, Ethiopia Dairy, Rwanda Dairy

Öz: Etiyopya ve Ruanda Afrika'daki gelişmekte olan ülkelerdir ve ekonomik durumların iyileştirilmesi için çeşitli projeler sürdürülmektedir. Son gelişmelerin başlıca alanlarından biri tarımdır. Tarım her iki ülkedeki çalışma çağındaki nüfusun büyük bir bölümünü istihdam etmektedir ve süt endüstrisi son yıllarda daha fazla görünür hale geliyor. Etiyopyalılar Afrika'daki en büyük hayvancılık sürüsünden birine sahiptir ve süt üretimini en üst düzeye çıkarmak için bir potansiyel vardır. Bununla birlikte, yoksulluk Etiyopya'da halen büyük bir sorundur ve bu sadece işsizliğin azaltılması ve gıda güvenliğinin artırılması için süt endüstrisine yatırım yaparak azaltılabilir. Etiyopya'daki mevcut ekonomik iklim, süt endüstrisinde yatırımların genişletilmesi için elverişli bir konudur ve bu, küçük üreticilere olan çiftçileri artırabilir ve motive edebilir. Eğer uygun yatırımlar yapılırsa, Etiyopya'daki süt endüstrisi olumlu sonuçlar doğuracaktır. Ruanda, Afrika'da bir umut ışığı. Ülkedeki iyi yönetişim seviyesi muhteşemdir ve diğer Afrika ülkelerin izleyeceği hızı ayarlayıp katkıda bulunur.Ruanda, ekonomisini daha büyük ölçekte ilerletiyor ve hükümetin politikalarını modernize etme isteği fark edilmeye değer bir şey. Süt endüstrisi kötü bir durumda, ancak USAID müdahalesi, sanayiyi modernize etmek için muazzam çabalar sarf etti. USAID tarafından yapılan eğitimden çiftçiler, besleme işlemcileri ve tüketiciler yararlandı. Ruanda aynı hızda devam ederse, süt endüstrisi gelişecek ve komşularıyla rekabet edebilecekler. Her ikisi de gelişmek için yeni teknolojilere ve eğitime daha fazla yatırım yapmaya ihtiyaç duyuyor çünkü bu ikisi uzun vadede önemli. Anahtar Kelimeler: Müdahaleler, Yatırım, Etiyopya Sütü, Ruanda Sütü.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Prof. Dr. Glenn Paul Jenkins.
Keywords: Banking and Finance; Dairyx Production; Rwanda; Ethiopia; Dairy industry; Economics; Interventions; Investment; Ethiopia Dairy; Rwanda Dairy